Physical volcanology and geological relationships of the jurassic ferrar large igneous province, antarctica - Elliot, David H; Fleming, Thomas H (Journal of Volcanology and Geothermal Research, 2008)
The Ferrar Large Igneous Province forms a linear belt for 3500 km along the Transantarctic Mountains, and as a geochemical province extends into southeastern Australasia. The principal components of the Ferrar are: intrusive - Ferrar Dolerite sills and dikes, and Dufek intrusion; pyroclastic - the Prebble, Mawson and Exposure Hill Formations; effusive - the Kirkpatrick Basalt. In terms of the three dimensional architecture of the Ferrar, a range of "facies" can be recognized in each of the principal components. The Ferrar province was initiated with a major episode of phreatomagmatism leading to formation of tephra cones and associated deposits, and near-surface vent structures. Activity switched to predominantly quiet effusion of alternating thick flood basalt flows and thin pahoehoe lobes and flows. Intrusive bodies were emplaced early, given the occurrence of dolerite clasts in tuff-breccias, but most sills were probably intruded after accumulation of extrusive rocks. Pre-existing rift structures played a major role in controlling the transport and distribution of the Ferrar magmas and the apparent centers of extrusive activity. The associated paleohydrology controlled the eruption styles. © 2008.
57 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/097-315-503-052-845 tex.type: [object Object]
Keywords: Antarctica; Basalt; East Antarctica; Ferrar; Ferrar Glacier; Flood basalt flows; Geochemistry; Geochronology; Jurassic; Magmas; Structural geology; Volcanic rocks; Volcanoes; Volcanology; dept.esc; flood basalt; large igneous province; magma; phreatomagmatism; pyroclastic deposit; tephra; volcanology